Hints for the busy housewife (London : Health & Cleanliness Council)
1939-05 1939 1930s 50 pages : illustrations FOREWORD TO THE EIGHTH EDITION WOMEN take a pride - and a very proper pride - in keeping themselves and their households clean. "Where there's dirt there's danger” continues to be the motto of the mother who has the health of the family as her first care. But if the busy housewife of the present day compares her lot even with that of her mother and grandmother, she will see that within her grasp are weapons far more effective and more numerous than they were able to employ. Science has recognized the importance of the housewife’s task and come to her aid, with the result that many duties, once real bugbears in the household routine, are now performed most effectively without stress and strain and without domestic upheaval. Take washing day for instance. There are now obtainable soaps, soap powders, and soap flakes especially made to give the housewife the greatest possible assistance in her laundry duties. The modern electric laundry appliances and various items of electrical cleaning apparatus are magical aids for the busy woman which, while not yet in use in the majority of homes, are becoming more generally adopted as electricity continues to be increasingly used for domestic purposes. By carefully choosing her washing and cleaning materials; by using modern equipment whenever possible and, where out-of-date equipment has to serve, keeping it in the best possible condition with cleanliness and care; by careful planning of daily routine; by taking thought for her personal hygiene and appearance — the happy housewife is never without a clean, bright overall — the housewife can do much to make her housework no longer a depressing labour but an interesting and pleasant duty. It is hoped that this little book may contain some useful hints. The Health and Cleanliness Council thanks Miss L.M. Mojer, who, when Matron of the Nursery Training School, Wellgarth Road, London, N.W.11, Miss M.E. Marsden, who, when Head of the Domestic Science Training College, Battersea Polytechnic, London, S.W.11, and Miss Helen Masters, present Head of the Domestic Science Training College, Battersea Polytechnic, London, S.W.11, for supplying photographs to illustrate this handbook. Page Two 177/5/8/1